2021
DOI: 10.9734/jpri/2020/v32i3831010
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Awareness of Healthcare Workers During the COVID-19 Outbreak; A Cross-Sectional Study

Abstract: Objective: COVID-19 has affected millions of people throughout the world and due to the high rate of its spread, it is very vital to protect the people who are at the frontlines of COVID-19 positive cases. In this study, we have analyzed the level of awareness among the Healthcare Workers (HCWs) and level of preparedness by the Healthcare Authorities (HCA) for the safety of HCWs. Study Design: Cross-sectional prospective study. Subjects and Methods: Study was conducted online, for 3 months, from Ju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 1 publication
1
4
0
Order By: Relevance
“…A majority of respondents believed that despite being vaccinated, it is still necessary to wear a face mask (89.8%) and avoid public gatherings (73.7%) to limit the spread of Omicron. Consistent with our study, participants from the study of Muhammad et al reported that face masking (75.7%) and social distancing (96.2%) are the essential precautionary measures to limit the spread of the COVID-19 pandemic [ 32 ]. Similar findings have been reported from Saudi Arabia [ 33 ] that face-masking (77.8%) and social distancing (78.0%) are even more critical than vaccination to prevent COVID-19 spread.…”
Section: Discussionsupporting
confidence: 89%
“…A majority of respondents believed that despite being vaccinated, it is still necessary to wear a face mask (89.8%) and avoid public gatherings (73.7%) to limit the spread of Omicron. Consistent with our study, participants from the study of Muhammad et al reported that face masking (75.7%) and social distancing (96.2%) are the essential precautionary measures to limit the spread of the COVID-19 pandemic [ 32 ]. Similar findings have been reported from Saudi Arabia [ 33 ] that face-masking (77.8%) and social distancing (78.0%) are even more critical than vaccination to prevent COVID-19 spread.…”
Section: Discussionsupporting
confidence: 89%
“…Coronavirus disease 2019 (COVID -19) has emerged as a global crisis that is caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). It was detected for the first time in Wuhan, China in December 2019 [1,2]. Due to its rapid and global spread, the World Health Organization (WHO) declared the outbreak as a pandemic by March 11, 2020 [3].…”
mentioning
confidence: 99%
“…Among the infected are hundreds of HCWs. More than fifty deaths of HCWs have been reported in Italy and this number continues to grow throughout the world [6].…”
mentioning
confidence: 99%
“…The resulting anxiety may interfere with the performance of their duties [1,8]. During the pandemic, the duty hours of HCWs have been increased and they often have to work with inadequate resources [6]. The increased workload may negatively impact the HCWs who have less time to focus on getting proper nutrition and adequate sleep [9,10].…”
mentioning
confidence: 99%